Extruder Component Repair on Extrusion Machine: Perbaikan Komponen Extruder Pada Mesin Ekstrusi - Arwiyono, Wiky Anjaya; Tjahjanti, Prantasi Harmi (Universitas Muhammadiyah Sidoarjo, 2024)
Practical work is a form of educational and vocational organization that is participated in by students so that students can work directly in the world of business, industry or fabrication. Practical work aims to prepare students to become productive people and be able to work directly in their respective fields. Students can also experience the production atmosphere experienced by professional engineering in a factory. This research process requires several materials and equipment as equipment in the design process as well as several methods. data collection and problem formulation in the form of morphological design. The method for repairing the screw extruder is re-poking the screw thread area which was proposed by the customer technician who said that the screw thread area was starting to wear out so it needed to be rejuvenated. Maintenance Preventive Maintenance. Re-priming or rejuvenating the threaded part because the threaded part has started to wear out. For example, in scheduling, for screw components until now there has been no regular maintenance or replacement to overcome damage. After the time of re-positioning the screw enters the turning stage to smooth the surface before the unevenness of the re-positioning or CV. Sumber Agung Widodo is a company that has complete manufacturing equipment that can produce various kinds of spare parts from various kinds of production machines. Various problems that often occur have an impact on the ongoing production process. Some of the causes include not only material factors, but human resource factors also influence production quality.